Ewing’s sarcoma of the mandible: A case report - GOWRI PANDARINATH, Bhandarkar; KUSHAL, Shetty (International Arab Journal of Dentistry (IAJD), 2012)
Ewing’s sarcoma of the jaw is a primitive malignant tumor of the bone. It is commonly seen in children and adolescents. Its occurrence in the head and neck region is unusual and generally involves most frequently the mandible rather than the maxilla. The present case discuss the clinical, diagnostic (radiographic, histopathologic) and therapeutic findings of an ES of the mandible in a 14-year-old boy. Early detection of such lesions is difficult because the signs and the symptoms do not appear until the lesion has progressed considerably. This case elucidates the importance of professional knowledge of the relevant aspects of malignant lesions such as Ewing’s sarcoma.